Profesi itu Komunitas Moral - Mikhael Dua (Respons: Jurnal Etika Sosial, 2020)
In the 19th century Max Weber, a German sociologist, predicted that the future of modern society would be determined by the development of the profession. In such a society, every type of job / position will ensure itself as a profession equipped with technical scientific skills and service specialties. These demands and hopes do not occur much in traditional societies. He acknowledged that the concept of a profession already exists in traditional societies, but is still very, very limited. Among them we know the professions of lawyers, doctors and priests. To obtain these three positions, a person apart from undergoing a long education must also express loyalty to the professional position. These two conditions are highly emphasized because the profession has a special task, namely to provide specific services that are needed by the community.